Healthcare costs in relation to kidney function among older people: the SCOPE study - Balducci, Francesco; Di Rosa, Mirko; Roller-Wirnsberger, Regina; Wirnsberger, Gerhard; Mattace-Raso, Francesco; Tap, Lisanne; Formiga, Francesc; Moreno-González, Rafael; Kostka, Tomasz; Guligowska, Agnieszka; Artzi-Medvedik, Rada; Melzer, Itshak; et al. (European Geriatric Medicine, 2024)
Purpose: In this study, a comprehensive analysis of costs of chronic kidney disease (CKD) was performed, to understand factors associated with the economic burden of the disease in a multicentre international framework. Methods: The impact on costs of demographics, socio-economics, clinical, and functional variables was tested in 2204 subjects aged 75 years or more attending outpatient clinics in Europe using a multicentre 2-year prospective cohort study. By means of collected resources consumption and unit cost data a comprehensive cost database was built and then investigated using multilevel regression modeling. Results: Overall, hospitalization, medications and specialist visits were the main cost items, with a notable variability among countries. Estimated yearly costs were 4478€ ± 9804€, rising up to 6683€ ± 10,953€ for subjects with estimated Glomerular Filtration Rate (eGFR) < 30. Costs increased significantly according to the severity of the disease, gender and age. Clinical and functional covariates were also significantly associated with CKD-related total costs, even after correcting for the inter-country variability. Conclusion: Findings corroborate the importance of multidimensional assessment of participants with CKD, as multimorbidity and functional disability produce a detrimental impact on participant’s prognosis and cost of care. Preservation of functional impairment and adequate management of comorbidities may thus help decreasing the overall consumption on health care resources in CKD patients, especially in older people.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Chronic kidney disease; Healthcare costs; Multicentre; Older people; Resources consumption